2021
DOI: 10.1002/ptr.7213
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties, therapeutic potential, and legal status of Cannabis sativa L.: An overview

Abstract: Marijuana, or Cannabis sativa L., is a common psychoactive plant used for both recreational and medicinal purposes. In many countries, cannabis‐based medicines have been legalized under certain conditions because of their immense prospects in medicinal applications. With a comprehensive insight into the prospects and challenges associated with the pharmacological use and global trade of C. sativa, this mini‐review focuses on the medicinal importance of the plant and its legal status worldwide; the pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 143 publications
0
39
0
Order By: Relevance
“…Particularly, Blasco-Benito et al [10] highlighted a similar or slightly greater potency of a THC-rich cannabis extract with respect to pure THC in reducing the viability of different breast cancer cells, although minor identified terpenes did not affect THC effects. Furthermore, several studies have reported the anticancer properties of cannabidiol in both in vitro and in vivo preclinical models [4,21,23,24]; recently some evidence about the anticancer activity of cannabichromene, β-caryophyllene, β-caryophyllene oxide, and α-humulene have been highlighted as well [4,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, Blasco-Benito et al [10] highlighted a similar or slightly greater potency of a THC-rich cannabis extract with respect to pure THC in reducing the viability of different breast cancer cells, although minor identified terpenes did not affect THC effects. Furthermore, several studies have reported the anticancer properties of cannabidiol in both in vitro and in vivo preclinical models [4,21,23,24]; recently some evidence about the anticancer activity of cannabichromene, β-caryophyllene, β-caryophyllene oxide, and α-humulene have been highlighted as well [4,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, supercritical fluid extraction of C. sativa was developed to contain more cannabinoids [ 31 ]. Cannabinoids have shown diverse remedial potential against depression, epilepsy, and other effects of clinical relevance [ 32 , 33 ]. Among the various pharmacological effects, several studies have reported an inhibitory effect of cannabinoids on CRC progression.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most successful strategies of targeting the ECS is based on Cannabis sativa or its specific phytocannabinoids. While they have proved effective in many indications , and are generally well tolerated, the therapy comes with a risk of addiction and adverse effects, such as memory impairment or cognitive dysfunctions caused by the long-term use . Thus, there is still room for improvement in this therapeutic area.…”
Section: Introductionmentioning
confidence: 99%